2002
DOI: 10.3354/meps238173
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and potential food chain transfer factor of Cd, Se and Zn in marine fish Lutjanus argentimaculatus

Abstract: Radiotracer techniques were employed to quantify the rates of uptake from aqueous and dietary sources, and rates of elimination of Cd, Se and Zn by a marine predatory fish, the mangrove snapper Lutjanus argentimaculatus. The relative significance of bioaccumulation of metals by fish from water and food and the food chain transfer factor were then assessed using a kinetic modeling approach. Cd and Zn in the aqueous phase exhibited an approximately linear uptake pattern over a 1 to 2 d exposure, whereas Se exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
117
8
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(149 citation statements)
references
References 52 publications
(92 reference statements)
22
117
8
2
Order By: Relevance
“…Our results on levels of gastrointestinal absorption are consistent with levels reported in various vertebrate experiments ranging from 0.5 to 16% (Neathery and Miller 1975;Xu andWang 2002, Hispard et al 2008;Mann et al 2006;Zalups and Ahmad 2003) according to the Cd-concentration in diet that individuals were fed. In our study, the proportional accumulation in liver and kidney depended on the amount of Cd ingested with decreasing assimilation efficiency when ingestion increased, suggesting that as the dose of Cd increases, assimilation decreases.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results on levels of gastrointestinal absorption are consistent with levels reported in various vertebrate experiments ranging from 0.5 to 16% (Neathery and Miller 1975;Xu andWang 2002, Hispard et al 2008;Mann et al 2006;Zalups and Ahmad 2003) according to the Cd-concentration in diet that individuals were fed. In our study, the proportional accumulation in liver and kidney depended on the amount of Cd ingested with decreasing assimilation efficiency when ingestion increased, suggesting that as the dose of Cd increases, assimilation decreases.…”
Section: Discussionsupporting
confidence: 80%
“…In reptiles and other vertebrates, Cd is mainly accumulated in liver, kidney, and pancreas and in the intestinal mucosa (Chan et al 2004;Mann et al 2007;Rie et al 2001;Vogiatzis and Loumbourdis 1998;Weigel et al 1984;Xu and Wang 2002). Intestinal mucosa is rather an organ of transport (Chan et al 2001), and once Cd is absorbed through gastrointestinal tracts into the bloodstream, Cd associates reversibly with plasma proteins (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Though, Zn is critical for aquatic organisms, including fishes; however, Zn becomes poisonous when it exceeds its maximum value. Many researchers have stated that dietary Zn is the fundamental reason for increased Zn in marine fish (Xu and Wang, 2002). The Zn concentrations in the muscles of fish documented in the literature elsewhere in the world, such as those of marine culture fishes collected from Hong Kong (20.1 μg/g to 68.3 μg/g, dry weight) (Wong et al, 2001) and those of different marine fish species captured from Tuzla Lagoon, Turkey (16.48 μg/g to 37.39 μg/g) (Dural et al, 2007), were higher than those observed during this study.…”
Section: Distribution Of Heavy Metals In Fish Speciesmentioning
confidence: 99%
“…Marine fish accumulate metals from both the waterborne and dietary phases, but the relative importance of these 2 potential sources remains less well understood (Willis & Sunda 1984, Dallinger et al 1987, Xu & Wang 2002. Previously, many studies have quantified the effects of metal pre-exposure, via either a dietary or waterborne phase, on the subsequent bioaccumulation by freshwater fish, especially using the rainbow trout as the model organism (Handy 1992, Hollis et al 2001, Kamunde et al 2002a,b, Niyogi & Wood 2003.…”
Section: Introductionmentioning
confidence: 99%